Weight loss: indication of brain damage and effect of combined normobaric oxygen and ethanol therapy after stroke. (20th June 2015) - Cai, Lipeng; Geng, Xiaokun; Hussain, Mohammed; Liu, Zongjian; Gao, Zhi; Liu, Shimeng; Du, Huishan; Ji, Xunming; Ding, Yuchuan
Abstract : Background and Purpose: Weight loss is commonly seen after stroke. However, there is paucity of data that objectively examines the relationship between weight loss and infarction. We have used two unique models of middle cerebral artery (MCA) occlusion in rats to determine if weight loss can be used as indicator for severity of brain damage and for beneficial effects of stroke therapy. Methods: Sprague-Dawley rats underwent MCA occlusion using the rat intraluminal filament or auto-thrombus stroke models. Reperfusion was established at different intervals by removing the intraluminal filament or injecting r-tPA, followed by treatment with either ethanol (EtOH), normobaric oxygen (NBO), NBO plus EtOH or no treatment. The extent of brain injury was determined using infarct volume and motor performance. Results: The intraluminal filament ischaemic model demonstrated a significant positive correlation between weight loss and infarct volume size after acute stroke, as well as compared to infarct volumes post-treatment with NBO, EtOH and NBO plus EtOH. There was also a positive significant correlation between weight loss and infarct volume size in the thromboembolism ischaemic model with or without treatment. Furthermore a positive correlation was observed between weight loss and deficit score in both ischaemic models. Discussion: Degree of weight loss after stroke is largely associated with severity of infarction as well as damage reduction after treatment administration.